Two-year cumulative patency of endovascular arteriovenous fistula - Beathard, Gerald A (J Vasc Access, 2019)
BACKGROUND AND OBJECTIVES: The recent advent of a device to create a proximal radial artery arteriovenous fistula using an endovascular approach to create the anastomosis represents a significant advance in dialysis access creation. This endovascular arteriovenous fistula offers the beneficial attributes of the proximal radial artery arteriovenous fistula while adding the advantages of avoiding a surgical procedure. The endovascular arteriovenous fistula can be created safely, functions well, has excellent patency, and has a high degree of patient satisfaction. The purpose of this study is to report the 2-year cumulative patency rate for a large multicenter cohort of endovascular arteriovenous fistula cases. DESIGN: An endovascular arteriovenous fistula was created in 105 patients using either local or regional anesthesia and conscious sedation. Patient data were obtained from each program’s electronic health record system. Data collection was truncated at 2 years postprocedure and used to calculate cumulative patency. Post-access creation patient satisfaction was assessed. RESULTS: A physiologically mature arteriovenous fistula (blood flow ⩾500 mL/min and a target vein internal diameter ⩾4 mm) was obtained in 98%. A clinically functional arteriovenous fistula (supporting two-needle dialysis according to the patient’s dialysis prescription) was demonstrated in 95%. Access failure resulting in the loss of access occurred in eight cases during the study period. The cumulative patency rate at 6, 12, 18, and 24 months was 97.1%, 93.9%, 93.9%, and 92.7%, respectively. The post-procedure patient evaluation emphasized a high level of patient satisfaction. CONCLUSION: The proximal radial artery arteriovenous fistula created using an endovascular approach for the anastomosis is associated with excellent 2-year cumulative patency and is associated with a high level of patient satisfaction.